Improving the Quality of Merdeka Curriculum Through Local Wisdom Based on Literary Works - Nur Frety Soumena; Rosmawaty Harahap (Winaya Inspirasi Nusantara Foundation, 2025)
Learning is an essential foundation in the development of a nation so that the curriculum has a crucial position in ensuring the quality of education. Unfortunately, the curriculum that is often used tends to be uniform and lacks attention to the local wisdom of a region. On the other hand, literary works reflect local wisdom and can be a rich and interesting source of education. The purpose of this research is to narrate efforts to improve the quality of the independent curriculum through literature-based local wisdom. This research uses a qualitative model with an exploratory literature research approach. The results of this study show that local wisdom based on literary works applied in the education process makes the younger generation more able to master, appreciate, and defend cultural values, and protect local wisdom and strengthen national identity. Thus, through the Merdeka Curriculum, which seeks to apply and apply local wisdom based on literary works, it can develop humans who have in-depth knowledge of local wisdom, maintain cultural values, and build a strong personality for the future.